2005
DOI: 10.1007/s10120-004-0313-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of S-1 and cisplatin combination therapy in patients with advanced or recurrent gastric cancer

Abstract: chemotherapy regimens using biochemical modulation and/or combination therapies have improved the prognosis of patients with gastric cancer. S-1 is an oral anticancer agent that was developed based on the theory of the biochemical modulation of 5-FU. S-1 is composed of tegafur (FT, a prodrug of 5-FU), 5-chloro-2,4-dihydroxypyridine (CDHP), and potassium oxonate (Oxo), at a molar ratio of 1 : 0.4 : 1 [1]. CDHP inhibits the biodegradation of 5-FU, and Oxo reduces 5-FUinduced gastrointestinal toxicities. In summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…S-1 has been approved in Japan for gastric, colorectal, head and neck, breast, pancreas, biliary tract, and lung cancer. In particular, S-1/cisplatin combined therapy has a high response rate (37-74%) for gastric cancer [26,27]. Cho et al [28] reported the efficacy of S-1/ cisplatin therapy for advanced esophageal cancer, and the response rate was 74.1% (20 out of 27 cases), including a pathological complete response rate of 18.5% in primary lesions.…”
Section: Discussionmentioning
confidence: 97%
“…S-1 has been approved in Japan for gastric, colorectal, head and neck, breast, pancreas, biliary tract, and lung cancer. In particular, S-1/cisplatin combined therapy has a high response rate (37-74%) for gastric cancer [26,27]. Cho et al [28] reported the efficacy of S-1/ cisplatin therapy for advanced esophageal cancer, and the response rate was 74.1% (20 out of 27 cases), including a pathological complete response rate of 18.5% in primary lesions.…”
Section: Discussionmentioning
confidence: 97%
“…In recent reports, this combination has been described to contribute to the long-term survival of these patients. 10,11 For these reasons, we selected S-1 in combination with CDDP for the present patient.…”
Section: Discussionmentioning
confidence: 99%
“…However, MST was 319 days and 322 days, respectively, which indicates that the therapies did not contribute in any way to the extension of survival time (18). Therefore, when chemotherapy is started with S-1 alone and it is found to be ineffective, it is expected that adding CDDP to the therapy does not shorten the survival time but, instead, it maintains the response rate with less incidence of sideeffects.…”
Section: Discussionmentioning
confidence: 99%